Reading the razor blade: the problematic reception of contemporary French extreme cinema - Parsons, Martin John Anthony (2013)
From the early 1990s onwards, a trend in French cinema took the body, especially the violated body, as the starting point of an engagement with the spectator which moved beyond the traditional ocular relationship between film and viewer and into a more physical mode. The reception of these films has been difficult, for a variety of reasons. In this dissertation we look at how this trend, herein described as Contemporary French Extreme Cinema, has been damaged by its critical reception, by its refusal to occupy understood cinematic spaces, and by censorship. The basis for the analysis herein rests in the phenomenological film analyses of Linda Williams, Vivian Sobchack and Laura Marks, through which we draw a new model for film spectatorship based on an awareness of genre and an understanding of the haptic rapport which these films engender. Analysis of this trend is complex, with a multitude of possible approaches, but this dissertation offers a series of suggestions which will hopefully assist in the navigation of such difficult territory. While it would be imprudent to claim to offer any firm conclusions on a trend that, we argue, might not yet be finished, this dissertation nonetheless suggests where the failures might lie, how these might be reclaimed, and how these films might have influenced French cinema as it stands today.